Pendidikan akhlak dalam perspektif susunan surah Al-Qur'an: studi kasus Surah Al-Ma'un dan Al-Kautsar - Fath, Amir Faishol; Usman, Dia Hidayati; Fath, Sholah El Madany (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This study aims to analyze and identify the moral education guidelines found in Surah Al-Ma'un and Surah Al-Kautsar, and how these two surahs complement each other in shaping the character of students. The research employs a qualitative approach, utilizing textual analysis to explore the themes and messages conveyed in both surahs. Surah Al-Ma'un emphasizes the importance of purifying oneself from negative traits, while Surah Al-Kautsar highlights the significance of cultivating noble character. By examining the interrelationship between these surahs, the study seeks to provide a comprehensive framework for moral education that can be applied in contemporary educational settings. The findings are expected to contribute to the development of effective character-building programs based on Islamic teachings, ultimately fostering a generation with strong moral value. AbstrakPenelitian ini bertujuan untuk menganalisis dan mengidentifikasi pedoman pendidikan akhlak yang terdapat dalam Surah Al-Ma'un dan Surah Al-Kautsar, serta bagaimana kedua surah tersebut saling melengkapi dalam membentuk karakter peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan analisis teks untuk mengeksplorasi tema dan pesan yang disampaikan dalam kedua surah. Surah Al-Ma'un menekankan pentingnya membersihkan diri dari sifat-sifat negatif, sementara Surah Al-Kautsar menyoroti signifikansi pengembangan akhlak mulia. Dengan memeriksa hubungan antara kedua surah ini, penelitian ini bertujuan untuk memberikan kerangka kerja yang komprehensif untuk pendidikan akhlak yang dapat diterapkan dalam konteks pendidikan modern. Temuan diharapkan dapat berkontribusi pada pengembangan program pembentukan karakter yang efektif berdasarkan ajaran Islam, yang pada akhirnya membentuk generasi dengan nilai-nilai moral yang kuat.